Phosphorus-doped silicon nanorod anodes for high power lithium-ion batteries - Yan, Chao; Liu, Qianru; Gao, Jianzhi; Yang, Zhibo; He, Deyan (Beilstein Journal of Nanotechnology, 2017)
Heavy-phosphorus-doped silicon anodes were fabricated on CuO nanorods for application in high power lithium-ion batteries. Since the conductivity of lithiated CuO is significantly better than that of CuO, after the first discharge, the voltage cut-off window was then set to the range covering only the discharge–charge range of Si. Thus, the CuO core was in situ lithiated and acts merely as the electronic conductor in the following cycles. The Si anode presented herein exhibited a capacity of 990 mAh/g at the rate of 9 A/g after 100 cycles. The anode also presented a stable rate performance even at a current density as high as 20 A/g.
Keywords: in situ reduction; lithium-ion battery; silicon anode; silicon nanorods